-6(3u-1)+5u=2(u+9)

Simple and best practice solution for -6(3u-1)+5u=2(u+9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(3u-1)+5u=2(u+9) equation:



-6(3u-1)+5u=2(u+9)
We move all terms to the left:
-6(3u-1)+5u-(2(u+9))=0
We add all the numbers together, and all the variables
5u-6(3u-1)-(2(u+9))=0
We multiply parentheses
5u-18u-(2(u+9))+6=0
We calculate terms in parentheses: -(2(u+9)), so:
2(u+9)
We multiply parentheses
2u+18
Back to the equation:
-(2u+18)
We add all the numbers together, and all the variables
-13u-(2u+18)+6=0
We get rid of parentheses
-13u-2u-18+6=0
We add all the numbers together, and all the variables
-15u-12=0
We move all terms containing u to the left, all other terms to the right
-15u=12
u=12/-15
u=-4/5

See similar equations:

| 88=-5x+3 | | -2(4y-3)-8y+6=4y(y-2) | | 3(u-2)=7u+4-2(-2u-2) | | 1.7x+8-1.62x0.4x-0.32=8 | | 5p·-5=150 | | 5x+7+x+6=10 | | 4y-4+2(3y+5)=-2(y+1) | | (3x-4)^2=-25 | | 8x-(5x+5=1 | | x+(x/4)=40 | | 6x+-8=6x+2 | | –0.4(3x+8)=–3x–3.2 | | k-18=23 | | x2+4x+437=0 | | (8x-7)+(2x+4)=127 | | -14w^2+20w-3=0 | | 2775.50=2600.00(1+0.75r) | | 42+4y=-13 | | 12(x-4)+7=25 | | 25+j=-14 | | 25+j=-11 | | 1314=730(1+0.16t) | | 2x+(x-6)=458 | | 2x+6+x+7=11 | | 2x+9=3x−17 | | 18c+3=2c+5 | | 4=75+x | | -4(x+2{x-4(3x-2)})=116(5x+8) | | 120+x+130=180 | | 5x+90=15 | | 0,96x*12,5=24 | | 40=14-2x |

Equations solver categories